2010
DOI: 10.1007/s11708-010-0118-6
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of EGR effects on reducing the pressure rise rate of HCCI engine combustion

Abstract: The effects of the inert components of exhaust gas recirculation (EGR) gas on reducing the pressure rise rate of homogeneous charge compression ignition engine combustion were investigated numerically by utilizing the CHEMKIN II package and its SENKIN code, as well as Curran's dimethyl ether reaction scheme. Calculations were conducted under constant volume combustion and engine combustion (one compression and one expansion only, respectively) conditions. Results show that with constant fuel amount and initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…As swirl ratio increases; lower peak pressures are obtained at any EGR concentration, but percentage reduction in peak pressures is high at higher swirl ratios and higher EGR concentrations. The reason for this phenomenon is increase in turbulence owing to increased wall heat transfer because of increased swirl ratios [28,29]. This study also indicated modest shift in the occurrence of maximum peak pressure towards TDC with increase in EGR concentrations [30].…”
Section: Exhaust Gas Recirculation (Egr)mentioning
confidence: 72%
See 1 more Smart Citation
“…As swirl ratio increases; lower peak pressures are obtained at any EGR concentration, but percentage reduction in peak pressures is high at higher swirl ratios and higher EGR concentrations. The reason for this phenomenon is increase in turbulence owing to increased wall heat transfer because of increased swirl ratios [28,29]. This study also indicated modest shift in the occurrence of maximum peak pressure towards TDC with increase in EGR concentrations [30].…”
Section: Exhaust Gas Recirculation (Egr)mentioning
confidence: 72%
“…They reported that with increase in EGR fraction retarded the start of combustion and decreased the peak pressure and temperature rise. Under the same conditions with increase in EGR ratio, extension in preparation of thermal ignition and advancement in LTHR timing were observed [7]. Swirl helps in homogeneous mixture formation of the fuel and air [8].…”
Section: Introductionmentioning
confidence: 99%
“…Calculation is carried out based on the following assumptions: (1) A premixed mixture is homogeneous. The LTHR starting is the timing where HRR reaches 1.0 J/CA and the HTHR starting is the timing where the mole fraction of H 2 O 2 reaches its maximum value [31]. (3) No heat transfer.…”
Section: The Calculation Methodsmentioning
confidence: 99%
“…The effects of the inert components of EGR gas on reducing of the pressure rise rate of homogeneous charge compression ignition engine combustion were investigated numerically in paper [8] by utilizing the CHEMKIN II package and its SENKIN code, as well as Curran's dimethyl ether reaction scheme. Calculations were conducted under constant volume combustion and engine combustion conditions (one compression and one expansion only, respectively).…”
Section: Dotychczasowy Stan Badańmentioning
confidence: 99%
“…Badania numeryczne wpływu obojętnych składników EGR na ograniczenie szybkości narastania ciśnienia w silniku HCCI, z wykorzystaniem pakietu CHEMKIN II, kodu SENKIN oraz schematu reakcji Currana dimetylu eteru, przeprowadzono w pracy [8]. Obliczenia prowadzono dla stałej objętości spalania i dla warunków silnika spalinowego (odpowiednio dla jednego suwu sprężania i jednego suwu rozprężania).…”
Section: Dotychczasowy Stan Badańunclassified